Art and Electronics : Video-Skulptur in Deutschland seit 1963. - Pao Galleries, Hong Kong; Hong Kong Arts Centre, Hong Kong (Hong Kong : European Working Group for Culture, 1995)
Jaffrennou, Michel ; Van Kerckhoven, Anne-Mie ; Latham, William ; Plessi, Fabrizio ; Shaw, Jeffrey ; Shiu, Carvien ; Torres, Francesc ; Werner, Agneta ; Anders, Anna ; Böhmler, Claus ; Brenner, Birgit ; vom Bruch, Klaus ; Günther, Ingo ; Guiton, Jean-François ; Kahlen, Wolf ; Diessling, Dieter ; Megert, Franziska ; Odenbach, Marcel ; Paik, Nam June ; Rosenbach, Ulrike ; Ruthenbeck, Reiner ; Staehle, Wolfgang ; Vostell, Wolf ; Wentscher, Herbert
Catalogus 3: Art and Electronics : Video Sculptures in Germany since 1963, 66 p. : ill., engelse tekst
Art and Electronics : Video-Skulptur in Deutschland seit 1963 / Video Sculptures in Germany since 1963, Pao Sui Loong and Pao Yue Kong Galleries, Hong Kong Arts Centre, Hong Kong, 16.02.95 - 05.03.95
boek